2019
DOI: 10.2355/isijinternational.isijint-2018-573
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Silico-Ferrite of Calcium and Aluminium (SFCA) Iron Ore Sinter Bonding Phase Formation: Effects of Basicity and Magnesium on Crystallisation during Cooling

Abstract: The effects of basicity and Mg addition on the crystallisation during cooling of complex Ca-rich ferrite iron ore sinter bonding phases SFCA and Fe-rich SFCA was investigated using in situ synchrotron X-ray diffraction. In synthetic iron ore sinter mixtures, cooling of a high temperature (T = 1 623 K) assemblage comprising magnetite and melt showed that decreasing basicity from B = 4.0 to 3.0 and 2.5 resulted in the formation of a Fe-rich SFCA phase being suppressed, with SFCA being the only Ca-rich ferrite ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…SFCA phase due to its acicular structure also helps in arresting crack propagation and improve both RDI and RI. 3,30,31) Few selected samples of varying RDI were analysed for phase quantification, and in line with the above findings, it can be observed that an increase in SFCA and Magnetite phase Fig. 9, RDI is also improved.…”
Section: Microstructural Analysis Of Plant Sintersupporting
confidence: 78%
“…SFCA phase due to its acicular structure also helps in arresting crack propagation and improve both RDI and RI. 3,30,31) Few selected samples of varying RDI were analysed for phase quantification, and in line with the above findings, it can be observed that an increase in SFCA and Magnetite phase Fig. 9, RDI is also improved.…”
Section: Microstructural Analysis Of Plant Sintersupporting
confidence: 78%
“…Secondly, the proper addition of Al 2 O 3 in the liquid phase of the sintering aids in the formation of acerous calcium ferrite. Webster et al [ 9 ] used in situ S-XRD (synchrotron X-ray diffraction) to study the effect of basicity on the crystallization of the effective bonding phase of SFCA (silico-ferrite of calcium and aluminum) and Fe-rich SFCA in the sinter during cooling. The formation of Fe-rich SFCA is inhibited when the basicity is decreased from 4.0 to 2.5, but SFCA crystallizes from the melt during the cooling of material with basicity of 2.5.…”
Section: Introductionmentioning
confidence: 99%
“…Quicklime has a finer particle size and better dispersion compared with other fluxes, thus it can be uniformly distributed in the material layer during the granulation process, which is beneficial for the formation of liquid phase SFCA during the sintering process, as a result, the sinter consolidation strength and yield is improved. 18,19) Secondly, the high material-temperature of the mixture play significant role in eliminating the over-wetting zone in sintering layer and improving the sintering indices. Active quicklime has a absolutely high content of CaO with released large amount of heat during digestion, which can effectively increase the temperature of the material mixture.…”
Section: Flux Structure Selectionmentioning
confidence: 99%